2011
DOI: 10.1039/c1cc15173h
|View full text |Cite
|
Sign up to set email alerts
|

Transforming terpene-derived aldehydes into 1,2-epoxides via asymmetric α-chlorination: subsequent epoxide opening with carbon nucleophiles

Abstract: Merging Jørgensen's and MacMillan's organocatalytic aldehyde chlorinations enables the synthesis of chiral vinylcyclopropanes and (-)-cis-aerangis lactone via terpene-derived 1,2-epoxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…In summary,w ehave carried out ad etailed investigation of the organocatalytic a-chlorination of aldehydes.I tw as possible to isolate and characterize the off-cycle intermediates for the first time,elucidate their role in the catalytic cycle and to suppress their accumulation. Remarkably,the catalyst loading was reduced from 20-30 mol % [6,8] to 5mol %. The new catalytic system was applied to av ariety of substrates where it demonstrated good functional group tolerance with excellent enantio-and diastereoselectivity.F or electron-rich olefins,allylic chlorination could be supressed with amodified reaction procedure capitalizing on the higher reactivity of enamines.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…In summary,w ehave carried out ad etailed investigation of the organocatalytic a-chlorination of aldehydes.I tw as possible to isolate and characterize the off-cycle intermediates for the first time,elucidate their role in the catalytic cycle and to suppress their accumulation. Remarkably,the catalyst loading was reduced from 20-30 mol % [6,8] to 5mol %. The new catalytic system was applied to av ariety of substrates where it demonstrated good functional group tolerance with excellent enantio-and diastereoselectivity.F or electron-rich olefins,allylic chlorination could be supressed with amodified reaction procedure capitalizing on the higher reactivity of enamines.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[5] During at otal synthesis campaign, we attempted to convert citronellal as terpene-feedstock into the corresponding 1,2-epoxide by a-chlorination, reduction and baseinduced epoxide formation. [6] Theapplication of MacMillans organo-SOMO methodology [2] led to decomposition which can be attributed to radical intermediates,w hich react with the electron-rich olefin within the substrate. [7] Expensive chlorinating reagents [4] or catalysts [1] were prohibitive for scale-up.M erging inexpensive N-chlorosuccinimide (NCS) 3 and MacMillansi midazolidinone 2·TFAr esulted in an efficient system that was used in our group [6,8] and by others.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Sharpless asymmetric epoxidation [15] of 22 afforded the corresponding epoxide (not shown) along with recovered alcohol (+)-22 in high enantiomeric purity (98 % ee) at 60 % conversion. [18] After some experimentation with this unusual substrate, we found that a combination of MacMillan's catalyst 26 [16] and NCS [18] gave a-chloroaldehyde 10 in optimal enantiomeric purity (85 % ee). The preparation of a-chloroaldehyde 10 involved a onecarbon homologation of commercially available alcohol 24 by displacement of the corresponding mesylate with cyanide and subsequent reduction.…”
Section: In2007kçnigreportedtheisolationofascospiroketals a (1)mentioning
confidence: 97%
“…In 2004, MacMillan [12], Lectka [13], and Jørgensen [14] reported the first catalytic highly enantioselective α-chlorination of aldehydes, acid chlorides, and ketones, respectively, using perchloroquinones and N-chlorosuccinimide (NCS) as chlorination reagents. After these preliminary works, the enantioselective α-chlorination of ketones [15] and aldehydes [16][17][18][19][20] has remained under study, other derivatives such as 1,3-dicarbonyl compounds [21][22][23][24][25][26][27], oxindoles [28,29], and silyl ketene acetals [30], being recently added to the nucleophile pool of this transformation. Regarding 1,3-dicarbonyl compounds, the best enantioselectivities have been obtained for cyclic β-ketoesters, which have been chlorinated in the α-position employing chiral alkaloid derivatives [21,25,27], chiral N,N 1 -dioxides [22], chiral amino diol derivatives [23], and chiral phase transfer catalysts [24,26].…”
Section: Introductionmentioning
confidence: 99%